Eugenol as a Potential Drug Candidate: A Review - Taleuzzaman, Mohamad; Jain, Pooja; Verma, Rishabh; Iqbal, Zeenat; Mirza, Mohd. A. (Current Topics in Medicinal Chemistry, 2021)
Eugenol is a bioactive compound widely available in many herbs like clove, cinnamon, tulsi, pepper etc. The compound is known for its antioxidant, antimicrobial, anesthetic, anti-inflammatory, neuroprotective, anti-diabetic, and anti-cancer activities. In pharmaceutical analysis, eugenol is used as a marker for single drugs and drug products. Dental care, household, and personal hygiene products are other areas where it has established its potential. In the food industry, eugenol is used as a flavouring agent in non-alcoholic beverages, baked foods, and chewing gums. Considering the huge potential of eugenol, this review is an attempt to collate the regulatory information, physico-chemical properties, toxicity profile, marketed conventional and novel formulations, analytical methods, extraction procedures, recent patents and clinical trials of the moiety. Based on literature survey a schematic diagram of mechanism of action has also been made.
Keywords: Pharmacological properties